Graphic Design Of “Green Mission” Education Game Using Software Based On Vector - Nur Yanti; Ridwan Sanjaya; FX. Hendra Prasetya (SISFORMA, 2017)
Educational game is a digital game in its design using the elements of education and in it support teaching and learning by using technology that is interactive media. Generally an educational game has a fun look, an easy-to-use menu, as well as color combinations that are used that are GUI-based (Graphic User Interface) so as to create appeal to users. Because it is undeniable that the human brain tends to more quickly capture learning through visual images rather than writings. Therefore, graphic design of an educational game becomes one of the important points. Software applications become one of the solutions in making game design, one of which is a vector-based software applications. There are various software that can be used in accordance with the function and usefulness of each. But in general the way the software works almost same.